Prevalence and severity of ectopic eruption of first permanent molars in 5–12-year-Old children attending a tertiary dental hospital in Dubai, United Arab Emirates - Ali Mohammed Akbar; Mawlood Kowash; Iyad Hussein; Anas Salami; Amar Khamis; Manal Al Halabi (Frontiers in Dental Medicine, 2026)
Background Ectopic eruption (EE) of first permanent molars (FPMs) is a developmental disturbance that can lead to premature loss of the second primary molar (SPM), space loss, and malocclusion if not detected early. Objective This retrospective, record-based cross-sectional review determined the prevalence and severity of FPM ectopic eruption among children in this Dubai tertiary-care cohort and compared findings with international data. Methods Dental records and radiographs from 962 children aged 5–12 years who attended a tertiary dental hospital in Dubai between 2020 and 2024 were reviewed. Ectopic FPMs were identified radiographically and classified into four grades according to SPM root resorption. Data were analyzed using chi-square and Fisher's exact tests, with statistical significance set at α = 0.05. Results Thirty-nine children (4.1%) had at least one ectopic FPM, corresponding to 61 affected teeth and a per-tooth prevalence of 1.6%. Ectopic eruption was more frequent in the maxilla than in the mandible, and patient-level bilateral involvement occurred predominantly in the maxilla. Most cases were mild, with severe cases being uncommon. No significant associations were found with sex, age group, nationality, or health status. Conclusion In this hospital-based Dubai cohort assessed across a broad 5–12-year age range using available diagnostic radiographs, FPM ectopic eruption showed a mid-range prevalence with a maxillary predilection. Early radiographic assessment and timely interceptive intervention remain important to prevent complications and support optimal occlusal development.